Eight-year follow-up of resurfacing hemiarthroplasty for advanced glenohumeral osteoarthritis following total acromionectomy. (16th August 2018) - Borton, Zakk; Ibrahim, Edward; Thomas, Kate; Rashid, Abbas
Abstract : Total acromionectomy is now a largely historical procedure due to a number of biomechanical sequelae caused by defunctioning of the deltoid, although its overall effect on joint kinematics is uncertain. This presents a challenge when considering arthroplasty for subsequent glenohumeral arthritis. We report on successful management of such a case, treated with resurfacing hemiarthroplasty 57 years following acromionectomy. The patient continues to enjoy excellent functional outcome of the shoulder at 8 years after arthroplasty.